2002
DOI: 10.1364/ol.27.001421
|View full text |Cite
|
Sign up to set email alerts
|

Simple technique for measuring the Goos–Hänchen effect with polarization modulation and a position-sensitive detector

Abstract: An original approach to directly measuring the Goos-Hänchen longitudinal shift between TE and TM polarization states during a total internal reflection is introduced. The technique is based on the modulation of the polarization state of a laser by an electro-optic modulator combined with a precise measurement of the resulting spatial displacement with a position-sensitive detector. This method presents many advantages over other techniques and allows measurements at different wavelengths over a broad range for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 8 publications
3
38
0
Order By: Relevance
“…This confirms that only the field in the vicinity of the optical vortex determines the C--line shift, and that the Gaussian envelope is less relevant. We note that, in our experiment, we did not have to use a very sensitive position detection method such as a split detector in combination with a lock--in amplifier as is common in beam--shift experiments [11], because the vortex core position can be determined with very high accuracy. More than 60 years ago Wolter [12], suggested that the nodal line of a pair of plane waves [13] should be easier to detect than the centroid of an optical beam; our experimental results confirm that suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms that only the field in the vicinity of the optical vortex determines the C--line shift, and that the Gaussian envelope is less relevant. We note that, in our experiment, we did not have to use a very sensitive position detection method such as a split detector in combination with a lock--in amplifier as is common in beam--shift experiments [11], because the vortex core position can be determined with very high accuracy. More than 60 years ago Wolter [12], suggested that the nodal line of a pair of plane waves [13] should be easier to detect than the centroid of an optical beam; our experimental results confirm that suggestion.…”
Section: Discussionmentioning
confidence: 99%
“…In the study reported in [22] . The use of a two-dimensional position-sensitive detector made it possible for Pillon et al [24] under conditions of a single total internal reflection to measure not only the longitudinal Goos-Hänchen shift, but also the much-smallerin-magnitude transverse Fedorov-Imbert shift.…”
Section: Spatial and Angular Shifts Incident To Refraction And Reflecmentioning
confidence: 96%
“…In [22] a single longitudinal Goos-Hänchen shift was measured using a one-dimensional position-sensitive detector. This method made it possible to determine with an accuracy of hundreds of nanometers the difference in the longitudinal shift for light polarized in the plane of incidence (р-polarization) and perpendicular to the plane of incidence (s-polarization).…”
Section: Spatial and Angular Shifts Incident To Refraction And Reflecmentioning
confidence: 99%
“…In addition to simple beam position monitoring, a few interesting applications of PSDs are worth citing: angle sensors [31,32], interferometry and phase measurements [25], Fourier transform spectrometry [33], and refractive index measurements [26,34]. PSDs have even been used for vortex beam calibration [35] or for measuring the Goos-Hänchen effect [36].…”
Section: Principlementioning
confidence: 99%